Lepidopteran Insects Status and Diversity: A Review - Nilufa Yasmin Poly; Shimanta Dutta; Ferdous Alam; Ahasan Ullah Khan (Pandawa Institute, 2023)
The second largest and most well-known insect order Lepidoptera includes both butterflies and moths in the world. This study was started based on secondary information from present literature from different countries on the flora and fauna. So far, much study work was completed on this subject but those workers were not existing to the extension employees, policymakers, and the public in an efficient way to date. In this review paper, we can give the recent data on etymology, distribution and diversity, external morphology, different morphological parts of caterpillar, internal morphology, digestive system, circulatory system, reproduction and growth, respiratory system, and growth and role of the olfactive process in larval and adult lepidopteran insects. There are over one hundred and eighty thousand Lepidoptera species described, divided into one hundred and twenty-six families and forty-six superfamilies, and the total number of living beings was labeled as about ten percent. A result found is that the species of moths is about one hundred sixty thousand compared to one hundred seventy thousand five hundred species of butterflies in the world. Butterflies are an important category of insects that can function as sensors of environmental change. Butterflies are insects from the order Lepidoptera's macro-lepidopteran clade Rhopalocera. The study focused on the lepidopteran insects and the diversity of the world. It presents the review of research imperfect data on specific knowledge in diverse agroecological zones. This study acknowledged investigating breaches in different countries of the world. It also provides information on lepidopterans as alternative food and financial source of the world. It also helps in the sustainable agricultural field.